PENGAWASAN NETRALITAS APARATUR SIPIL NEGARA (ASN) PADA PILKADA KOTA SORONG TAHUN 2017 - Elias Idie (SOSCIED, 2023)
The dynamics of organizing direct elections is a process of free competition that requires the role of actors and supporting systems, to win the struggle for regional head power. Some interesting issues discussed are how the Neutrality of Civil Servants in the Regional Election with a Single Candidate and the pattern of Civil Servant Neutrality Violations during the Campaign and the Implementation of Panwaslu Supervision of Civil Servant Neutrality Violations. The data approach in this research is carried out using the method of literature study, laws and regulations, indirect interviews with closed and open questions through questionnaires with sources or informants including civil servants in the Sorong City government and direct interviews with sources of Panwaslu Commissioners for the 2017 period. The implementation of regional elections in Sorong City in 2017 was to obtain or maintain positions, the existence of primordial relationships, lack of understanding of regulations related to neutrality, other factors such as pressure from superiors, low integrity of civil servants, the assumption that not being neutral is commonplace and the weakness of the bureaucratic system, news both in print, online, and electronic media, and others. Because of the factors that cause ASN not to be neutral in the elections, because of the importance of maintaining and maintaining the career of positions / positions. It is necessary to evaluate the neutrality of the prevention and supervision system for civil servants, which has been promoting appeals and socialization, by building an inherent and collaborative supervision system.